2001
DOI: 10.1002/dev.1012
|View full text |Cite
|
Sign up to set email alerts
|

Early maternal rejection and later social anxiety in juvenile and adult Japanese macaques

Abstract: This study investigated the relationships between early maternal style and subsequent juvenile and adult behavior of offspring in Japanese macaques (Macaca fuscata). Early maternal style had no effect on baseline behavior of offspring when adult. In contrast, early maternal style was correlated with the response of adult offspring to stressful social interactions, and particularly with their response to actual or potential aggression. Infants whose mothers encouraged more independence showing high rates of rej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 30 publications
2
30
0
1
Order By: Relevance
“…We classified mothers into four different groups on the basis of their maternal style (Fairbanks & McGuire, 1988) to test the hypothesis that different mothering styles were correlated with the behavioral repertoire of infants at three different ages (5, 7, and 9 months) during their development. In particular, in accordance with previous studies (Schino et al, 2001;Simpson, 1985;Simpson & Simpson, 1986;Suomi, 1987), we expected that infants of rejecting mothers would show higher frequencies of behaviors connected with the precocial development of motor skills, such as locomotion and exploration, and would show a higher level of enterprise associated with a higher frequency of interaction with other group members. We also would expect infants of protective mothers to be less interested in the external environment, to be more cautious, and less inclined to initiate contact with other group members (Fairbanks & McGuire, 1988;Andrews & Rosenblum, 1993;Vochteloo, Timmermans, Duijghuisen, & Vossen, 1993).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…We classified mothers into four different groups on the basis of their maternal style (Fairbanks & McGuire, 1988) to test the hypothesis that different mothering styles were correlated with the behavioral repertoire of infants at three different ages (5, 7, and 9 months) during their development. In particular, in accordance with previous studies (Schino et al, 2001;Simpson, 1985;Simpson & Simpson, 1986;Suomi, 1987), we expected that infants of rejecting mothers would show higher frequencies of behaviors connected with the precocial development of motor skills, such as locomotion and exploration, and would show a higher level of enterprise associated with a higher frequency of interaction with other group members. We also would expect infants of protective mothers to be less interested in the external environment, to be more cautious, and less inclined to initiate contact with other group members (Fairbanks & McGuire, 1988;Andrews & Rosenblum, 1993;Vochteloo, Timmermans, Duijghuisen, & Vossen, 1993).…”
supporting
confidence: 54%
“…Finally, this work provides a link with recent findings by Schino et al (2001) studying the effect of maternal style on the later behavior of adult Japanese macaques. They found that baseline adult behavior is not affected by maternal style.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In contrast, infants reared by more protective mothers appear to be delayed in the acquisition of their independence and are relatively fearful and cautious when faced with challenging situations ( Fairbanks & McGuire, 1987Vochteloo et al , 1993 ). Effects of mothering style on offspring behavior have been shown to extend into adulthood ( Fairbanks & McGuire, 1988 ;Schino et al , 2001 ;Bardi et al , 2005 ;Bardi & Huffman, 2006 ;Maestripieri et al , 2006b ). These effects have also been demonstrated with experimental manipulations of maternal behavior ( Vochteloo et al , 1993 ) and with infant cross-fostering studies ( Maestripieri, 2005a, b ;Maestripieri et al , 2006b ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, infants reared by more protective mothers appear to be delayed in the acquisition of their independence and are relatively fearful and cautious when faced with challenging situations (Fairbanks and McGuire 1987, 1988Vochteloo et al 1993). Effects of parenting style on offspring behavior can extend into adulthood McGuire 1988, 1993;Schino et al 2001;Bardi et al 2005; Bardi and Huffman 2006;Maestripieri et al 2006b). These effects have also been demonstrated with experimental manipulations of maternal behavior (Vochteloo et al 1993) and with infant crossfostering studies (Maestripieri 2005,b;Maestripieri et al 2006b).…”
Section: Introductionmentioning
confidence: 99%